Contribution of -1031T/C and -376G/A tumor necrosis factor alpha polymorphisms and haplotypes to preeclampsia risk in Tunisia (North Africa). (February 2022) - Raguema, Nozha; Ben Ali Gannoun, Marwa; Zitouni, Hedia; Ben letaifa, Dhafer; Seda, Ondrej; Mahjoub, Touhami; Lavoie, Julie L.
Highlights: The minor allele TNF-α -1031C polymorphism is associated with preeclampsia. -1031C and -376A (CA) haplotype was associated with a higher incidence of preeclampsia. The TG haplotype seems to be associated with a reduced prevalence of preeclampsia. Abstract: Preeclampsia is a gestational disorder characterized by hypertension and proteinuria. Excessive release of pro-inflammatory cytokines, particularly tumour necrosis factor-alpha, has been demonstrated to contribute to endothelial activation and poor trophoblast invasion in placental development, resulting in preeclampsia's clinical symptoms. Genetic polymorphisms of tumour necrosis factor-alpha can regulate its production and may play an important role in the pathogenesis of this disease. This study aimed to evaluate the association of five tumour necrosis factor-alpha gene promoter single nucleotide polymorphisms, or their haplotype combinations, with preeclampsia prevalence. This case-control study was conducted on 300 women with preeclampsia and 300 age-matched women with normal pregnancy from Tunisian hospitals. Genotyping of tumour necrosis factor-alpha −1031 T/C, −376 G/A, −308 G/A, −238 G/A, and +489 G/A SNPs was performed on DNA extracted from blood samples using PCR-restriction fragment-length polymorphism analysis. Statistical analysis was performed using the chi-square test. P < 0.01 were considered statistically significant to take into consideration the multiple comparisons. A significantly higher frequency of the minor allele -1031C (p < 0.001) was observed in preeclampsia cases compared to controls. Notably, the -1031C and -376A (CA) haplotype, which correlates with a higher production of TNF-α protein, had a higher incidence in women with preeclampsia (p = 0.0005). Conversely, the TG haplotype had a low frequency in preeclampsia cases compared to controls (p = 0.002) which suggests that it is associated with a reduced incidence of preeclampsia. These results suggest that tumour necrosis factor-alpha polymorphisms, in particular the -1031C/A, and the haplotype CA, contribute to an increased risk of preeclampsia in Tunisian women.